Transformasi Pendidikan Kewarganegaraan Dalam Era Digital - Abdel Haris Aragati; Eka Widiastuti; Muhammad Luthfillah Andria; Ilham Hudi; Rendi Satya Saputra (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The advancement of the era has witnessed unparalleled upheaval in the dissemination of data worldwide. This mechanical progress has infiltrated every aspect of human relations. One field impacted by this digital transformation is education. This article aims to understand the importance of data innovation in civic education, which can provide tremendous benefits in shaping a younger generation informed about civic education. In this study, we employ a literature review method to investigate phenomena related to Civic Education Transformation. We meticulously gather and analyze various sources, including books, scholarly journals, and other publications relevant to our topic. The transformation of civic education in the digital era is an adaptive and innovative process responsive to the development of information technology. Digitalization has significant impacts on civic education, both positively and negatively. On one hand, digitalization enables broader and faster access to information, allowing students to access various sources of civic education information. With this digitalization, students can easily search for information, thus enhancing efficiency in learning activities. However, this digital era is not without challenges that must be addressed. To address these challenges, it is essential to implement civic education values expected to realize Indonesia's educational vision in creating the profile of Pancasila learners.